Airway obstruction and inflammation on combined bronchoscopy in children with Down syndrome. Issue 9 (20th July 2021) - Vielkind, Monica; Wolter‐Warmerdam, Kristine; Jackson, Arwen; Maybee, Jennifer; Brown, Mark; Friedlander, Joel; Friedman, Norman; Hickey, Francis; Prager, Jeremy; Wine, Todd; DeBoer, Emily
Abstract: Objective: To characterize the upper and lower airway findings in children with Down syndrome and chronic respiratory symptoms, based on evaluation by flexible bronchoscopy (FB) with bronchoalveolar lavage and microlaryngoscopy with bronchoscopy (MLB). Study design: A retrospective review was conducted of children with Down syndrome aged 1 month to 17 years, who underwent both FB and MLB within a 1‐year timeframe between 2010 and 2019 at Children's Hospital Colorado. Anatomic airway findings are reported as frequencies within the cohort. Bronchoalveolar lavage fluid (BALF) culture results, cell differential, and cytopathology are reported as frequencies or mean ± standard deviation. BALF results were compared between children with and without dysphagia documented on a recent swallow evaluation. Results: Overall, 168 children with Down syndrome were included, with median age of 2.1 years (interquartile range: 0.9–5.1 years). At least one abnormal airway finding was recorded in 96% of patients and 46% had at least three abnormal findings. The most common findings included tracheomalacia (39% FB; 37% MLB), subglottic stenosis (35% MLB), pharyngomalacia (32% FB), and laryngomalacia (16% FB; 30% MLB). Comparison of BALF based on dysphagia status showed that children with dysphagia had more frequent cultures positive for mixed upper respiratory flora (76% vs. 47%, p = 0.004) and a higher percentage of neutrophils (20% vs. 7%, p = 0.006). Conclusion: Abnormal findings for FB and MLB are common in children with Down syndrome and chronic respiratory symptoms, and performing the procedures together may increase the diagnostic yield.